2018
DOI: 10.1161/jaha.118.008884
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension and Risk of Clinical and Subclinical Cardiovascular Disease in Middle‐Aged Adults

Abstract: BackgroundAlthough orthostatic hypotension (OH) is a well‐recognized manifestation of neuropathy and hypovolemia, its contribution to cardiovascular disease (CVD) risk is controversial.Methods and ResultsParticipants with OH, defined as a decrease in blood pressure (systolic ≥20 mm Hg or diastolic ≥10 mm Hg) from the supine to standing position, were identified during the first visit of the ARIC (Atherosclerosis Risk in Communities) Study (1987–1989) within 2 minutes of standing. All participants were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 50 publications
1
64
2
5
Order By: Relevance
“…Eight studies reported data about the relationship between OH and heart failure . The pooled result demonstrated a positive relationship between OH and HF (summary HR 1.34, 95% CI 1.17‐1.52, P < 0.001), with moderate heterogeneity ( I 2 = 48.7%).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Eight studies reported data about the relationship between OH and heart failure . The pooled result demonstrated a positive relationship between OH and HF (summary HR 1.34, 95% CI 1.17‐1.52, P < 0.001), with moderate heterogeneity ( I 2 = 48.7%).…”
Section: Resultsmentioning
confidence: 95%
“…In total, 1462 articles were retrieved from the literature, of which four articles had the same population. We chose the article written by Juraschek et al for its long follow‐up. Finally, 15 met the inclusion criteria and were included in the meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations